Effect of processing on the air void system of 3D printed concrete. (June 2022) - Das, Arnesh; Song, Yu; Mantellato, Sara; Wangler, Timothy; Lange, David A.; Flatt, Robert J.
Abstract: The long-term performance of 3D printed concrete structures involves various durability issues, and in this study, we are focusing on frost damage. This can be a serious issue in cold places like Switzerland and may be particularly problematic for 3D printed structures owing to the likely presence of cold joints. 3D printing often involves processing steps such as pumping, set acceleration and extrusion, and in the present work, we consider the effect of these processing conditions on the air void system. It was found that pumping and extrusion processes significantly change the void structure while acceleration or higher setting rates can stabilize them, the latter ensuring a higher protection from frost damage. It was also seen that after extrusion, cast and printed samples have very comparable void systems and spatial distribution of voids, implying no clear impact of the presence of interfaces in the latter.